2007
DOI: 10.1016/j.mycres.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

In planta selfing and oospore production of Phytophthora cinnamomi in the presence of Acacia pulchella

Abstract: This paper provides the first evidence of A2 type 1 and type 2 isolates of Phytophthora cinnamomi producing selfed oospores in planta in an Australian soil and in a potting mix. Oospores were observed in infected lupin (Lupinus angustifolius) roots incubated for 7 d either in the substrate under potted Acacia pulchella plants, or in soils collected from under and near varieties of A. pulchella in jarrah (Eucalyptus marginata) forest. The A2 type isolates varied in their ability to produce selfed oospores and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…can also stimulate selfing within heterothallic oomycetes (Brasier 1971(Brasier , 1978Jayasekera et al 2007;Jung et al 2013;Lamour and Kamoun 2009). Differences between forest and nursery systems in terms of these environmental factors could cause different rates of selfing which, in turn, could affect genetic differences between the two systems.…”
Section: Discussionmentioning
confidence: 99%
“…can also stimulate selfing within heterothallic oomycetes (Brasier 1971(Brasier , 1978Jayasekera et al 2007;Jung et al 2013;Lamour and Kamoun 2009). Differences between forest and nursery systems in terms of these environmental factors could cause different rates of selfing which, in turn, could affect genetic differences between the two systems.…”
Section: Discussionmentioning
confidence: 99%
“…P. cinnamomi is ostensibly heterothallic although sexual reproduction through selfing does occur in the A2 mating type in the presence of external agents such as Trichoderma spp. (Brasier, , ,b; Pratt, Sedgley, Heather, & Shepherd, ) and in Acacia roots (Jayasekera, McComb, Shearer, Hardy, & St, ). Crone, McComb, O'Brien, and Hardy () showed that the A2 mating type formed abundant selfed oospores in naturally infected roots of several herbaceous plants showing no symptoms of disease and postulated that the formation of selfed oospores in plant roots was probably common and widespread on asymptomatic hosts.…”
Section: What Does Genetic Variation In A1 Phytophthora Cinnamomi Telmentioning
confidence: 99%
“…Although P. cinnamomi is a heterothallic species, it can be difficult to get oospores to form when pairing isolates of opposite mating type and, when oospores do form, they can be difficult to germinate (16)(17)(18)32,44). However, Linde et al (23) and Dobrowolski et al (7) were successful in obtaining oospores from sexual outcrosses with sufficient germination frequency to allow analysis of the progeny.…”
mentioning
confidence: 99%
“…The ability of isolates to self and form oospores in single culture in response to different environmental stimuli has been reported but, again, the oospores are difficult to germinate (32,41,48). Interestingly, Jayasekera et al (16) observed selfing of isolates in colonized roots of Lupinus angustifolis when placed in soil underneath Acacia pulchella. The occurrence of sexual recombination in populations of P. cinnamomi is important because this could assist with long-term survival of the pathogen in the form of persistent oospores as well as increasing the potential for genetic diversity of the pathogen.…”
mentioning
confidence: 99%